Improving Students’ Vocabulary Mastery through Fun Thinkers Media: : Case Study for the First Year- Autistic Students of SMP Negeri 3 Hutabayuraja - Melisa Carolina Sianturi; Sahlan Tampubolon; Lastri W. Manurung (Journey: Journal of English Language and Pedagogy, 2023)
This research examines the vocabulary knowledge abilities of autistic students in English subjects at SMP Negeri 3 Hutabayuraja. According to Zuchdi (1995: 3-7) vocabulary mastery is a person's ability to recognize, understand and use words well and correctly by listening, speaking, reading and writing.The research's formulation of the issue is "Does vocabulary knowledge skills be improved through Fun Thinkers media for the first year Autistic students of SMP Negeri 3 Hutabayuraja". The purpose of the current research is to ascertain whether linguistic abilities among autistic pupils have increased as a result of exposure to Playful Philosophers materials. The method of gathering information is being tested. Five autistic children in class VII at SMP Negeri 3 Hutabayuraja served as the study's participants. This research uses an experimental method, namely using Single Subject Research (SSR) with an AB design. The usage of Fun Thinkers media can enhance vocabulary knowledge abilities for the first-year Autistic students at SMP Negeri 3 Hutabayuraja, according to the findings of the data analysis and.discussion above. It.can be seen that.the.provision of interventions in.the form.of Vocabulary Learning through fun thinkers’ media shows an increase in scores forRH students and the improvement obtained is quite good